Dampak Penggunaan Media Sosial Tiktok Terhadap Perilaku Anak Usia Sekolah Dasar - Azizah, Muthia; Nurfarida Deliani; Juliana Batubara (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of writing this article is to find out how the impact of using TikTok social media on the behavior of elementary school-age students, because elementary school-age children are very vulnerable to the influence of social media, especially TikTok. Recently, one of the most used social networks is TikTok and it has caused concern among parents and teachers, because this TikTok social media can be accessed anywhere and anytime, and for the content displayed is also very diverse. The writing method used is a qualitative descriptive method with data collection techniques using literature studies and interviews. Library research conducted on previous research and books related to this material, as well as interviews with teachers, parents and students. From this presentation, it was obtained the results of his research that TikTok social media can have a positive impact on children if directed and supervised by parents, and it will have a negative impact on children if children access social media freely without parental supervision. For this reason, parental supervision is needed so that TikTok can have a positive impact on elementary school-age children. Because in addition to useful content or videos, there are also a lot of videos and content that are not good for consumption by children and even adults